2021
DOI: 10.1136/bmjsem-2021-001043
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of mental health symptoms among male and female Australian professional footballers

Abstract: ObjectiveDetermining the prevalence of mental health symptoms (MHS) among Australian professional footballers compared with former players. A secondary aim was to assess whether MHS were associated with recent injury and psychological resilience.MethodsThis cross-sectional study included 149 male (mean age: 24 years) and 132 female (mean age: 23 years) Australian A-League and W-League professional footballers (study group) and 81 former male footballers (control group, mean age: 39 years) for analysis. MHS and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 32 publications
3
26
1
1
Order By: Relevance
“…Two additional international cross-sectional studies using the same assessment method identified adverse nutritional behaviours in 47.4–74.3% of male players [15, 16]. Within the recent Australian cross-sectional study [23], 35.1% of current male players, 43.8% of current female players and 40.0% of former male players reported disordered eating behaviours via the Brief Eating Disorder in Athletes Questionnaire (BEDA-Q) [47].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Two additional international cross-sectional studies using the same assessment method identified adverse nutritional behaviours in 47.4–74.3% of male players [15, 16]. Within the recent Australian cross-sectional study [23], 35.1% of current male players, 43.8% of current female players and 40.0% of former male players reported disordered eating behaviours via the Brief Eating Disorder in Athletes Questionnaire (BEDA-Q) [47].…”
Section: Resultsmentioning
confidence: 99%
“…The majority of studies were cross-sectional in design (n=9), but two case-control studies, an observational prospective cohort study and a retrospective cohort study were also reviewed. The studies sampled male (n=7), female (n=4) and mixed-sex (n=2) populations, examining mood (11 studies) [14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24], anxiety (10 studies) [14, 15, 16, 17, 18, 19, 21, 22, 23, 25], distress/burnout (6 studies) [14, 15, 16, 17, 18, 23], disordered eating (5 studies) [14, 15, 16, 17, 23], sleep disturbance (6 studies) [15, 16, 17, 18, 23, 26], alcohol use (6 studies) [14, 15, 17, 18, 23, 24], substance misuse (1 study) [23] and gambling (1 study) [23]. Full details of the studies are reported in Table 1…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations